2020
DOI: 10.3390/ijerph17103478
|View full text |Cite
|
Sign up to set email alerts
|

Using Life History Calendars to Estimate in Utero and Early Life Pesticide Exposure of Latinx Children in Farmworker Families

Abstract: (1) Background: Early life exposure to neurotoxic chemicals can have later impacts on child health. Most research designs must assume that current exposure is similar to past. Life history calendar methods can help to provide data on early life exposure. (2) Methods: Life history calendars were completed by mothers of 8-year-old children from Latinx farmworker and non-farmworker families (n = 73 and 65, respectively). Measures were created of months exposure through living adjacent to farm fields and having ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Additional details of the larger study can be found elsewhere. 24 The current study used a telephone survey to reach the mother of the children in these families in May 2020. These mothers answered questions for themselves, their children, and for other family members.…”
Section: Methodsmentioning
confidence: 99%
“…Additional details of the larger study can be found elsewhere. 24 The current study used a telephone survey to reach the mother of the children in these families in May 2020. These mothers answered questions for themselves, their children, and for other family members.…”
Section: Methodsmentioning
confidence: 99%
“…The larger study uses a comparative design, with a sample of families of Latinx farmworkers with children and a sample of similar families but without any farmworker members. Additional details of the study can be found elsewhere [27]. The current study used a telephone survey to reach the mother of the children in these families in May 2020, when no face-to-face contact between study staff and study participants was permitted by the Institutional Review Board due to COVID-19-related health concerns for research participants.…”
Section: Methodsmentioning
confidence: 99%
“…Additional details of the larger study can be found elsewhere. 24 The current study used a telephone survey to reach the mother of the children in these families in May, 2020, when no face-to-face contact between study staff and study participants was permitted by the Institutional Review Board due to COVID-19-related health concerns for research participants. All procedures, including the telephone survey, were approved by the Wake Forest University Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%